Electrospun polycaprolactone/silk fibroin nanofiber scaffold with aligned fiber orientation for articular chondrocyte regeneration - Xie, Bowen; Yang, Fengyuan; Chen, Hongguang; Zhang, Hongxing; Ma, Hebin; Li, Tianqi; Chen, Zhiqiang; Li, Jingyuan; Li, Xiaojie; Du, Junjie (Frontiers in Materials, 2023)
Electrospun nanofibers exhibit potential as scaffolds for articular cartilage tissue regeneration. This study aimed to fabricate electrospun polycaprolactone (PCL)/silk fibroin (SF) composite nanofiber scaffolds and to explore performance of the scaffolds for articular chondrocyte regeneration. By altering material composition and preparation methods, three types of nanofiber scaffolds were effectively fabricated, including randomly oriented PCL (RPCL) nanofiber scaffold, randomly oriented PCL/SF (RPCL/SF) nanofiber scaffold, and aligned PCL/SF (APCL/SF) nanofiber scaffold. Physiochemical analyses were performed to determine mechanical properties and surface hydrophilicity of the nanofiber scaffolds. In vitro studies were conducted to investigate performance of the scaffolds on articular chondrocyte proliferation, gene expression and glycosaminoglycan secretion. Cytoskeleton staining was used to observe the arrangement of chondrocytes along the direction of the fibers and their elongation along the fiber arrangement. The physicochemical analysis demonstrated that the APCL/SF nanofiber scaffold exhibited improved mechanical properties and surface hydrophilicity compared to the RPCL and RPCL/SF nanofiber scaffolds. Furthermore, the in vitro cell culture studies confirmed that the APCL/SF nanofibers could significantly promote articular chondrocyte proliferation, type II collagen (COL-II) gene expression, and glycosaminoglycan secretion compared to the RPCL and RPCL/SF nanofiber scaffolds. Additionally, cytoskeletal staining displayed that the APCL/SF nanofiber scaffold promoted the elongation of articular chondrocytes in the direction of parallel fiber alignment. As a result, the APCL/SF nanofiber scaffold exhibited promising potential as a composite scaffold for articular cartilage regeneration.